Energy Design and Optimization of a Greenhouse: A Heating, Cooling and Lighting Study - Belkadi, A.; Mezghani, D.; Mami, A. (Engineering, Technology & Applied Science Research, 2019)
This paper presents a new approach to properly optimize the energy consumption in a greenhouse. An improved intermediate modeling to establish the energy balance in a greenhouse within a higher precision was adopted. While the classical model focuses on the efficient cooling and heating demands and neglects the profound impact of lighting parameters, it was shown that these three necessary components are interdependent, and they should be taken into account all together to comfortably reach optimal crop production and energy consumption. This study’s contribution is the classical model’s improvement and the demonstration of the fact that the heat released by the luminaries and the energy used by this equipment has fundamental consequences on the energy balance as well as the preferred choice of the possible shape of the greenhouse and its adequate cover.